Does employment protection create its own political support? - Björn Brügemann (Institute for the Study of Labor (IZA), 2006)
This paper investigates the ability of employment protection to generate its own political support. A version of the Mortensen-Pissarides model is used for this purpose. Under the standard assumption of Nash bargaining, workers value employment protection because it strengthens their hand in bargaining. Workers in high productivity matches benefit most from higher wages as they expect to stay employed for longer. By reducing turnover employment protection shifts the distribution of match-specific productivity toward lower values. Thus stringent protection in the past actually reduces support for employment protection today. Introducing involuntary separations is a way of reversing this result. Now workers value employment protection because it delays involuntary dismissals. Workers in low productivity matches gain most since they face the highest risk of dismissal. The downward shift in the productivity distribution is now a shift towards ardent supporters of employment protection. In a calibrated example this mechanism sustains both low and high employment protection as stationary political outcomes. A survey of German employees provides support for employment protection being more strongly favored by workers likely to be dismissed.
Keywords: 330